Thematic analyses of participant survey responses following dermatology ECHO programs with dermoscopy: Practical tips and lessons learned - Black, T. Austin; Parbs, Joshua R.; Teixeira, Anthony J.; Cyr, Peggy; Nelson, Kelly C.; Stoddard, Henry; Seiverling, Elizabeth V. (Frontiers in Digital Health, 2023)
Introduction: Skin cancer is a major public health concern in the United States, reflecting approximately one in every three cancer diagnoses. Despite the high incidence of skin cancer, access to dermatologists is limited, especially in rural areas. Primary care physicians play a pivotal role in the evaluation of skin conditions, but dermatology training gaps exist in primary care training programs. Objectives: This study examines the use of the Project ECHO (Extension for Community Healthcare Outcomes) knowledge-sharing framework to provide dermoscopy and skin cancer detection training to Primary Care Providers (PCPs). Methods: Analysis of surveys administered to participants in two separate dermoscopy-focused project ECHO courses was performed. Survey responses were collected over a four-year period for the two courses, held in Maine and Texas. Thematic analysis was performed on the qualitative data, revealing codes and subcodes that demonstrate overall trends. Results: Overall, most respondents indicated the ECHO sessions to be helpful, signifying an increase in confidence and knowledge in dermoscopy. Other codes identified a positive reception of learning materials and teaching styles. Furthermore, participant survey analyses highlighted areas of improvement for future ECHO course sessions. Conclusions: This thematic analysis of Dermatology Project ECHOs with dermoscopy demonstrates the ability to use virtual educational platforms to effectively teach PCPs about dermoscopy and skin cancer, with high satisfaction. The importance of keeping the educational sessions brief, avoiding sessions on high-volume patient care days, and determining a means for participants to obtain hands-on training to operate a dermatoscope were amongst the top lessons learned.